PEMIKIRAN DAN PERANAN SAYYID IDRUS BIN SALIM ALJUFRI TERHADAP PERKEMBANGAN PENDIDIKAN ISLAM DI MANADO - Rasyid, Lisa Aisyiah; Supriadi, Supriadi; Aisa, Siti (Journal of Islamic Education Policy, 2018)
Abstrack. As one of the scholars of the hadramain who played an important role in the development of islamic education in the eastern region of Indonesia, It is important to understand how the thinking and role of sayyid, the iraniacal bin salim aljufri, especially in the tower of the thousand churches, the city of manado. When Indonesia is beset by two themes of political persecution, fierce debate over islamic relations and countries between "secular" and religious nationalists, and the struggle between the hadrami of loyalty and integrity against the land between Indonesia or hadramaut. As one of the scholars of hadrami in the eastern region of Indonesia (kti), the old teacher did not get caught up in the political ideology of the political ideology, focusing on the movement: education, the preaching work, and the social empowerment, to the establishing of an alkhairaat islamic college in 1930. In 1934, the old master sent one of his disciples, muhammad qasim maragau for the preaching of the manado. In 1947 the official alkhairaat opened a branch in the town of manado, north sulawesi, to the rest of the istiqlal (Arab village), the following year in 1960 became a boarding school. From 1960 to 1996 the number of islamic islamic educational institutions of alkhairaate in sulut including manado steadily rises up to 167 branches, 2 of which is a boarding school located in the city of manado.Keywords:Guru Tua, Alkhairaat,Thought, role, Manado Abstrak. Sebagai salah satu ulama hadramain yang berperan penting terhadap perkembangan pendidikan Islam di Kawasan Timur Indonesia, penting kiranya untuk memahami bagaimana pemikiran dan peran Sayyid Idrus bin Salim Aljufri khususnya di wilayah Menara Seribu Gereja, Kota Manado. Ketika Indonesia dilanda oleh dua tema diskursus politik yang terjadi, yaitu perdebatan sengit tentang hubungan Islam dan negara antara kaum nasionalis “sekuler” dan nasionalis religious, dan pergumulan di kalangan Hadrami tentang loyalitas dan integritas terhadap tanah air antara Indonesia atau Hadramaut. Sebagai salah ulama Hadrami di wilayah Kawasan Timur Indonesia (KTI), Guru Tua tidak terjebak pada perdebatan ideologi politik tersebut, justru memfokuskan diri pada gerakan: pendidikan, dakwah, dan pemberdayaan sosial, hingga mendirikan sebuah perguruan Islam Alkhairaat pada tahun 1930. Pada tahun 1934, Guru Tua kemudian mengutus salah seorang muridnya, Muhammad Qasim Maragau untuk berdakwah ke Manado.Pada tahun 1947, Alkhairaat resmi membuka cabang di Kota Manado, Sulawesi Utara, tepatnya di Kelurahan Istiqlal (kampung Arab), yang selanjutnya pada tahun 1960 berkembang menjadi sebuah pondok pesantren. Sejak tahun 1960 hingga 1996 jumlah lembaga pendidikan Islam Alkhairaat di Sulut termasuk Manado terus meningkat hingga menjadi 167 cabang, 2 diantaranya adalah pondok pesantren yang berlokasi di kota Manado.Kata kunci: Guru Tua, Alkhairaat, Pemikiran, Peran, Manado.